Functıons And Challenges Of The Indonesıa's Busıness Competıtıon Supervısory Commıssıon In The Era Of Industrıal Revolutıon 4.0 - Elza Syarief; Indra Hengky (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Monopolistic practices and unfair business competition are needed to be regulated to protect both businessmen and consumers. The sovereignty of business competition law can be strengthened if the Indonesia's Business Competition Supervisory Commission/IBCSC (Komisi Pengawasan Persaingan Usaha/KPPU) can carry out its functions optimally, particularly in the era of Industrial Revolution 4.0 (IR 4.0). This research aims to ascertain whether the IBCSC can be perform its functions in enforcing business competition rules and what challenges it faces in performing its duties in the era of IR 4.0. This research applied a normative legal method and analyzed the data by using qualitative approaches. It found the IBSCS has authority to impose administrative sanctions against business actors who violate Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (Law No.5 of 1999). Unfortunately, the supervisory function of the IBCSC pertaining electronic systems is not regulated by this Law. Although a Memorandum of Understanding (MoU) and Cooperation Agreement between the Ministry of Communication and Information Technology (Menkominfo) and the IBCSC facilitates the enforcement and supervisory of business competition law in the IR 4.0, it cannot strengthen the IBCSC’s legal position as an institution. Therefore, it is strongly suggested to amend Law No. 5 of 1999 to cover transactions in the digital market to strengthen the functions and authorities of the IBCSC.